El control adaptativo en instalaciones existentes y su potencial en el contexto del cambio climático. - Sánchez-García, Daniel (Universidad del Bío-Bío, Chile, 2017)
Currently, energy consumption is high in most office buildings mainly due to the use of HVAC systems, which achieve thermal comfort without considering the energy implications. The objectives of this research are to reduce energy demand and consumption while maintaining high levels of adaptive thermal comfort, based on the application of adaptive setpoint temperatures calculated according to CEN Standard EN 15251, and to identify the potential of these procedures for the years 2020, 2050 and 2080, in the context of climate change. To that end, a five-stage methodology was carried out, which consisted of: (1) data collection; (2) field work involving monitoring building temperature and conducting thermal comfort surveys; (3) validation of the simulation model, according to temperature, Predicted Mean Vote (PMV), and energy consumption; (4) simulations; and (5) results. The method was implemented in a recently constructed building in Seville (Spain) that complies with current regulations. The results reveal important reductions in energy demand and consumption, with values between 52% and 63%, and between 51% and 61%, respectively, depending on the climate scenario analyzed.